Health-related quality of life in Thai patients with hepatocellular carcinoma and its influencing factors: A cross-sectional study - Thitiporn Pathomjaruwat; Yaowarat Matchim; Jane M. Armer (Belitung Nursing Journal)
Background: Health-related quality of life (HRQoL) is a critical indicator in individuals with cancer. Patients diagnosed with hepatocellular carcinoma (HCC) commonly experience a decline in HRQoL due to both the progression of the disease and the adverse effects associated with treatment. Despite the high prevalence of HCC in Thailand, there is a paucity of research examining the HRQoL of Thai patients and the factors that may influence it.